The Association Between Psoriasis and Cardiovascular Diseases - Ahmed Zwain; Mohanad Aldiwani; Hussein Taqi (European Cardiology Review)
Cardiovascular diseases and psoriasis have been well established as separate entities, however, there is uncertainty with regards to a link between the two diseases. A few environmental, psychological and social factors have been implicated as potential common risk factors that may exacerbate the two diseases, and an array of complex immune and non-immune inflammatory mediators can potentially explain a plausible link. Pharmacotherapy has also played a role in establishing a potential association, especially with the advent of biological agents which directly act on inflammatory factors shared by the two diseases. This review will look at existing evidence and ascertain a potential correlation between the two.